(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The nexus between criminal and terrorist groups constitute an increasing security threat to the EU, especially in the area of the abuse of the financial system for the purposes of terrorist financing as the associated predicate offence of money laundering (hereinafter: terrorist financing). In that regard, Directive (EU) 2015/849 on the prevention of the use of the financial system for the purposes of money laundering or terrorist financing constitutes the main EU legal instrument not only in the context of the detection and investigation but also the prevention it from occurring. However, emerging new trends, in particular regarding the way terrorist groups finance and conduct their operations, including those related to the misuse of prepaid cards and virtual currencies, have brought to light. On the other side, it is noted that there is lack of appropriate cooperation between financial intelligence units and with law enforcement authorities, especially in the area of the access to relevant information of financial organizations on transactions involving high-risk third countries. Therefore, it became undisputed that the Directive (EU) 2015/849 should be amended. In that context, the EU has adopted on 30 May 2018 amended Directive (EU) 2018/843 so as to include the changes to Directive (EU) 2015/849. This is precisely the main reason why the first part of the paper covers the new EU rules in identifying the financial operations of terrorist networks as well as in detecting their financial backers. Furthermore, since the objective of Directive (EU) 2018/843, namely the protection of the financial system by means of prevention, detection and investigation of terrorist financing, cannot be sufficiently achieved only by the Member States with individual measures adopted by them to protect their financial systems, it seems compulsory to take into consideration significant improvements achieved in this area at international level in order to examine whether the new amended EU framework is in compliance with existing international standards. For that reason, the second part of the article deals with the international standards on combating terrorist financing, especially those made by the Financial Action Task Force. Finally, since the Republic of Serbia has, in the context of accession and negotiations process to EU, recently adopted the new framework concerning money laundering and terrorist financing, the third part of the paper is dedicated to the analysis of the national framework in this area in order to examine its compliance with EU framework. In concluding remarks, it is noted that although in the recent period there have been significant improvements in the framework on terrorist financing and money laundering both at the international and EU level but also at the national level, there is still lack of effective implementation of adopted standards. Bearing in mind the above, some recommendations for accelerating the implementation of adopted measures on preventing terrorist financing are listed.